Pharmacokinetics of oral tetrahydrocannabinol and cannabidiol in humans: a systematic critical review (2021)
ABSTRACT: Background. The therapeutic potential of cannabis has aroused a growing interest among health professionals. Currently, medicines and phytotherapeutics containing cannabis derivatives such as tetrahydrocannabinol (THC) and cannabidiol (CBD) are marketed; however, the pharmacokinetic data of these products are scant. Objective. The aim of this review was to systematically collect the data published in this area. Methods. A systematic review of the literature was carried out in the PUBMED / MEDLINE, Current Contents, LILACS, Scielo databases, in search of all the articles that included THC and CBD pharmacokinetic data in humans, administered orally with exact doses. Results. After applying inclusion criteria, 14 studies were found. In general, it is described that absorption increases in the company of high-fat foods, repeated doses prolonged the half-life, the products have extensive body distribution, and liver damage increased the maximum concentration reached by derivatives, forcing reduction in the dose. Kidney failure does not significantly influence the pharmacokinetics of CBD. The maximum doses used were 35 mg of THC and up to 6000 mg of CBD. No serious adverse events were reported. However, due to the differences between formulations in the net content of the derivatives, the purity of the products and the heterogeneity of the population, it is not possible to generalize the pharmacokinetic parameters of these studies. Conclusion. More and better studies are required to establish a safer and more effective dosage for each medicinal cannabis formulation. Keywords: Medical Marijuana, cannabis, cannabinoids, cannabidiol, pharmacology, pharmacokinetics. PROSPERO registration number: CRD42019125831 Key Points: - Knowledge about the temporal course of the concentrations and quantities in the body of cannabis derivatives and metabolites is needed for a safe prescription of cannabinoids. - More studies with greater power in their methodological design are required in order to make recommendations for population use of medicinal cannabis.